Trade Liberalization, Antidumping, and Safeguards: Evidence from India's Tariff Reform - Bown, Chad P.; Tovar, Patricia (2012)
This paper is the first to use product-level data to examine empirically whether countries use antidumping and safeguard exceptions to unwind commitments to lower tariffs in the face of domestic political-economic pressure. We focus on the case of India, a country that underwent a major exogenous tariff reform program in the early 1990s and subsequently initiated substantial use of safeguard and antidumping import restrictions. We first estimate structural determinants of India's import protection using the Grossman and Helpman (1994) model and provide evidence from its pre-reform tariff data of 1990 that is consistent with the theory. We then re-estimate the model on the Indian tariff data after the trade liberalization is complete and find that the model no longer fits, a result consistent with theory and evidence provided in other settings that India's 1991-1992 IMF arrangement can be interpreted as resulting in an exogenous shock to India's tariff policy. However, when we re-estimate the model on data from 2000-2002 that more completely reflects India's cross-product variation in import protection by including both its post-reform tariffs and its additional non-tariff barriers of antidumping and safeguard import protection, the significance of the Grossman and Helpman model determinant estimates is restored. We interpret these combined results as evidence that India unwound its commitment to reduce tariffs through use of antidumping and safeguard protection in the face of political-economic pressure. The estimates are also economically important and provide one explanation for separate results in the literature that the magnitude of import reduction associated with India's use of antidumping is similar to the initial import expansion associated with its tariff reform. Finally, we interpret the implications of our results for the burgeoning research literature examining the effects of liberalization on India's micro-level development.